The Effect of Service Quality and Brand Image on Purchasing Decisions for Iphone Smartphones with Customer Value as an Intervening Variable (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Departing from the phenomenon that shows the number of iphone smartphone users increasing to reach 1.38 billion units in 2023, and a global market share of 28.01%. In September 2024 iphone sales jumped up to 5.51%. The variables that explain the phenomenon of iphone purchasing decisions are still diverse which then leads to the formulation of problems regarding the iphone smartphone purchase decision. From these problems, this study develops a research model that is empirically tested to explain again the variables that can influence purchasing decisions, using data obtained from distributing questionnaires to 119 respondents and processed using AMOS 24. The test results show that service quality and brand image have a positive and significant effect on purchasing decisions and customer value, customer value has a negative and significant effect on purchasing decisions, and customer value cannot mediate between service quality and purchasing decisions and brand image on purchasing decisions.
Keywords: service quality, brand image; purchasing decisions; customer value